Assessment of selected coated urea in enhancing nitrogen use efficiency in oil palm seedling growth - Hassan, Mardhati Hazirah (2018)
Sustainable cultivation of agricultural crops on the highly weathered, low nutrient soils of Malaysia requires adequate fertilizer input and proper soils management. Effective management of plants in terms of nutrient, especially nitrogen (N) is important because it highly influences plant growth and yield. However, N losses are often high in tropical soils due to denitrification, volatilization and leaching processes causing economic loss and environmental problems. A potential management of N is needed to overcome the problems through coated urea as slow release fertilizer. Thus study was conducted to determine the efficacy of coated urea as a means of improving nitrogen-use efficiency (NUE) with the aim of minimizing nitrogen loss and increasing its uptake. Nitrogen availability were quatified in 2 different types of soils (mineral soils and peat soil). A total of six treatments were evaluated , namely; common uncoated urea (U), geopolymer coated urea (GeoU), biochar coated urea (BioU), copper coated urea (CuU), zinc coated urea (ZnU), and copper-zinc coated urea (CuZnU) in both incubation and polybag studies. A laboratory study was first conducted to determine the effects of coated urea on Nitrogen availability in a mineral soil (an Oxisolss belonging to Munchong series) and in peat (organic soil). Treatment BioU (42%N) and CuZnU (36%N) gave the most significant result in mineral soil, with both treatments had positive Nitrogen availabilitys and N availability exhibited in ammonium release, nitrate release, urea-N retention and reduction of ammonia loss (by volatilization) (302.95 ug g-1- BioU, 333.83 ug g-1 - CuZnU). In contrast , CuU (43%N), ZnU (36%N) and CuZnU (34%N) gave higher N availability in peat with respective values of 287.24 ug g-1, 303.00 ug g-1 and 341.94 ug g-1. The cumulative ammonia volatilization percentage in treatments with CuU, ZnU and CuZnU also resulted in low ammonia loss with values 4.96%, 5.57% and 5.23% respectively. In conclusion, after 8 weeks of incubation, CuZnU was found the best coated urea treatment for bothpeat and mineral soils with high amount of urea-N retained, reflecting the slow release effects and low N losses. The treatments were further examined in a nursery study on oil palm seedlings grown in polibegs containing mineral soil (Munchong series) and peat (organic soil), which wascarried out in open field environment at Ladang 2, UPM for 12 months. This study involved 3 sampling time (6, 9 and 12 months seedling age) to evaluate the effects of coated urea on oil palm seedlings growth and nitrogen uptake in both soils. Application of coated urea significantly P (<0.05) improved oil palm growth and NUE by 7-10 % compared to control (uncoated urea). In mineral soil, oil palm seedlings treated with BioU and ZnU performed better with increased chlorophyll contents ( BioU at 6 and 9 months old, ZnU at 12 months old), higher plant height ( BioU found at 6 and 9 months old) and biomass (dry weight) (BioU – 6 and 9 months old, ZnU – 12 months old). Notably, at the second harvest (9 months old) and third harvest (12 months old), seedlings treated with BioU and ZnU were shown to increase N uptake and NUE. Meanwhile in peat, increased chlorophyll, plant height and dry weight were observed in oil palm seedlings grown in treatment of urea coated with micronutrients (CuU, ZnU and CuZnU).Oil palm seedlings treated with CuZnU showed increased N uptake at 6 and 12 months, and similar observation was observed in ZnU and CuU treatments at 9 and 12 months, respectively. Similar trend in N uptake also reflected the NUE. This can be attributed to the fact that nitrogen in coated urea are readily and slowly available for plant uptake over a given period of time. Biochar coated urea (BioU) have showed the best performance in mineral soil in both experiments, notably in highly significant urea N until week 8, increased nitrogen uptake and NUE in all stage (6 months old, 9 months old and 12 months old). The use of biochar as the coating material have positive effect on the soil and plant dynamic with increased nutrient availability, improved moisture holding capacity and improved nutrient holding capacity, thus making the soil fertile for agricultural activities (Lehman and Joseph, 2009;Rao et al.,2012). Meanwhile in peat, application of copper-zinc coated urea (CuZnU) showed the best effects in terms of urea N transformation to available form of N (ammonium and nitrate release), urea N, and stimulation in oil palm seedlings growth performance (N uptake and NUE). Coating micronutrients (copper and zinc) to urea also helped to slow down hydrolysis process, with both acting as urease inhibitors (Junejo et al.,2012; Khan et al., 2015). Furthermore, copper and zinc are micronutrients required for good plant growth. Thus, for the best coated urea efficacy and improved plant N uptake, coating urea with combination of Cu and Zn can be considered and further inspected. In conclusion, coated urea with waste material especially biochar, or with combination of micronutrients especially Zn and Cu has the potential as effective N fertilizer choices in increasing nitrogen uptake, NUE as well as in decreasing N losses (reducing ammonia loss) in oil palm seedlings cultivation.